BMP signaling components in embryonic transcriptomes of the hover fly Episyrphus balteatus (Syrphidae) - Lemke, Steffen (BMC genomics, 2011)
In animals, signaling of Bone Morphogenetic Proteins (BMPs) is essential for dorsoventral (DV) patterning of the embryo, but how BMP signaling evolved with changes in embryonic DV differentiation is largely unclear. Based on the extensive knowledge of BMP signaling in Drosophila melanogaster, the morphological diversity of extraembryonic tissues in different fly species provides a comparative system to address this question. The closest relatives of D. melanogaster with clearly distinct DV differentiation are hover flies (Diptera: Syrphidae). The syrphid Episyrphus balteatus is a commercial bio-agent against aphids and has been established as a model organism for developmental studies and chemical ecology. The dorsal blastoderm of E. balteatus gives rise to two extraembryonic tissues (serosa and amnion), whereas in D. melanogaster, the dorsal blastoderm differentiates into a single extraembryonic epithelium (amnioserosa). Recent studies indicate that several BMP signaling components of D. melanogaster, including the BMP ligand Screw (Scw) and other extracellular regulators, evolved in the dipteran lineage through gene duplication and functional divergence. These findings raise the question of whether the complement of BMP signaling components changed with the origin of the amnioserosa.